Media Systems, Politics and Press Freedom: Perspectives on Contemporary Russia and Nigeria - Sadrettin, Halil; Bayram, Pelin; Emeagwali, Lawrence (International Review of Management and Marketing, 2016)
The political system in any society is a major determinant of the nature of its media system. The policies of political leaders are key factors to ensuring the establishment and implementation of laws which promote the freedom of the press. This can be said of the Russian federation and Nigeria two prominent countries in Europe and Africa which have witnessed several political and media transitions over the years. From autocratic and repressive communist and military regimes respectively; Russia and Nigeria currently operate democratic models of governance with constitutions providing for the freedom of expression and of the press. Old habits seem to die hard as censorship and cases of assaults on journalists occur frequently contrary to global expectations of a free Russian and Nigerian press in the twenty-first century. Analysis of statistical data from two internationally respected media bodies; Reporters without Borders and Freedom House reveal that press freedom in Nigeria has improved in recent years amidst current setbacks from current religious and political crisis. Russia's press freedom index is still poor with an uncertain future. Being a measure of national development and international reputation; the Russian and Nigerian governments need to implement laws and policies which promote the freedom of the press. Keywords: Media System, Press Freedom, Russia and Nigeria. JEL Classification: L82